Strengthening anticipatory action in Zambia: a practical workshop on utilizing CGIAR and Zambia Red Cross Society solutions - Jeya Raj, Renuka; Alahacoon, Niranga; Amarnath, Giriraj; Wina, W. (International Water Management Institute, 2024)
Zambia, a country rich in natural resources and biodiversity, is increasingly vulnerable to the escalating threat of climate-related shocks, particularly droughts and floods. These extreme weather events have far-reaching consequences, disrupting livelihoods and severely undermining food security nationwide. In this context, traditional reactive disaster response methods are inadequate, often arriving too late to prevent significant humanitarian crises.